2021
DOI: 10.3389/fimmu.2021.744530
|View full text |Cite
|
Sign up to set email alerts
|

Inverted CD8 T-Cell Exhaustion and Co-Stimulation Marker Balance Differentiate Aviremic HIV-2-Infected From Seronegative Individuals

Abstract: HIV-2 is less pathogenic compared to HIV-1. Still, disease progression may develop in aviremic HIV-2 infection, but the driving forces and mechanisms behind such development are unclear. Here, we aimed to reveal the immunophenotypic pattern associated with CD8 T-cell pathology in HIV-2 infection, in relation to viremia and markers of disease progression. The relationships between pathological differences of the CD8 T-cell memory population and viremia were analyzed in blood samples obtained from an occupationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 71 publications
(111 reference statements)
1
12
0
Order By: Relevance
“…In parallel with the plasma collection, absolute CD4 + T-cell counts and CD4 + T-cell percentages of lymphocytes were performed using the FACS Presto instrument (BD Biosciences). 26 HIV-1 and HIV-2 pVLs were previously determined. 26 , 32 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel with the plasma collection, absolute CD4 + T-cell counts and CD4 + T-cell percentages of lymphocytes were performed using the FACS Presto instrument (BD Biosciences). 26 HIV-1 and HIV-2 pVLs were previously determined. 26 , 32 …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we and others have shown that both viremic and aviremic PLWH2 display signs of immune pathology, such as expansion of activated and exhausted CD4 + and CD8 + T-cells, B-cells, natural killer cells (NK-cells), NK T-cells (NKT), monocytes, and dendritic cells (DCs). 23 , 24 , 25 , 26 , 27 , 28 , 29 Interestingly, HIV-2 RNA and Gag protein have been found in peripheral blood mononuclear cells and lymphoid tissue of aviremic PLWH2, indicating ongoing viral replication despite having undetectable plasma viral load. 30 , 31 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic stimulations on tumor-infiltrating Tex cells induce high expression of Eomes, which downregulates CD226 (67,96,97). The Eomes-dependent loss of CD226 limits TCR signaling and antitumor effects (98)(99)(100)(101). Moreover, the loss of CD226 has been found to impair T cell response to PD-1 blockade (102)(103)(104).…”
Section: Co-stimulatory Moleculesmentioning
confidence: 99%
“…In chronic infection with HIV-1 and HIV-2, downregulation of CD226 has been observed in the peripheral blood: increased CD226 - PD-1 + antigen-specific CD8 + T cells correlated with increased viral load ( 26 , 27 ). CD226 downregulation also occurs in antigen-specific CD8 + T cells in mice chronically infected with LCMV clone 13, a common model used to evaluate T cell exhaustion.…”
Section: The Role Of Activating Receptors In T Cell Exhaustionmentioning
confidence: 99%